Synergistic Antibiofilm Action of Cinnamomum verum and Brazilian Green Propolis Hydroethanolic Extracts against Multidrug-Resistant Strains of Acinetobacter baumannii and Pseudomonas aeruginosa and Their Biocompatibility on Human Keratinocytes - Meccatti, Vanessa Marques [UNESP]; Martins, Karoline Moura Chagas [UNESP]; Ramos, Lucas de Paula [UNESP]; Pereira, Thaís Cristine [UNESP]; de Menezes, Raquel Teles [UNESP]; Marcucci, Maria Cristina [UNESP]; Abu Hasna, Amjad [UNESP]; de Oliveira, Luciane Dias [UNESP] (MDPI, 2023)
The accumulated dental biofilm can be a source of oral bacteria that are aspirated into the lower respiratory tract causing ventilator-associated pneumonia in hospitalized patients. The aim of this study was to evaluate the synergistic antibiofilm action of the produced and phytochemically characterized extracts of Cinnamomum verum and Brazilian green propolis (BGP) hydroethanolic extracts against multidrug-resistant clinical strains of Acinetobacter baumannii and Pseudomonas aeruginosa, in addition to their biocompatibility on human keratinocyte cell lines (HaCaT). For this, High-performance liquid chromatography analysis of the plant extracts was performed; then the minimum inhibitory and minimum bactericidal concentrations of the extracts were determined; and antibiofilm activity was evaluated with MTT assay to prevent biofilm formation and to reduce the mature biofilms. The cytotoxicity of the extracts was verified using the MTT colorimetric test, evaluating the cellular enzymatic activity. The data were analyzed with one-way ANOVA and Tukey’s tests as well as Kruskal–Wallis and Dunn’s tests, considering a significance level of 5%. It was possible to identify the cinnamic aldehyde in C. verum and p-coumaric, caffeic, and caffeoylquinic acids as well as flavonoids such as kaempferol and kaempferide and Artepillin-C in BGP. The combined extracts were effective in preventing biofilm formation and reducing the mature biofilms of A. baumannii and P. aeruginosa. Moreover, both extracts were biocompatible in different concentrations. Therefore, C. verum and BGP hydroethanolic extracts have bactericidal and antibiofilm action against multidrug resistant strains of A. baumannii and P. aeruginosa. In addition, the combined extracts were capable of expressively inhibiting the formation of A. baumannii and P. aeruginosa biofilms (prophylactic effect) acting similarly to 0.12% chlorhexidine gluconate.
Keywords: Acinetobacter baumannii; Cinnamomum verum; HaCaT Cells; propolis; Pseudomonas aeruginosa